2017
DOI: 10.1590/1980-5373-mr-2017-0618
|View full text |Cite
|
Sign up to set email alerts
|

B-N Codoped p Type ZnO Thin Films for Optoelectronic Applications

Abstract: The success of codoping by donor-acceptor impurities in accomplishing p type ZnO thin films deposited by spray pyrolysis technique is reported here. Monodoping ZnO with N altered the conductivity type but the resistivity is too high making it practically impossible to be useful in optoelectronic applications. B-N codoping increased the carrier concentration and obtained comparatively low resistivity because codoping enhanced the acceptor incorporation by forming acceptor-donor-acceptor complex in the band gap.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The E g values calculated for all samples are numerically tabulated in Table 1. It is visible from the table that the pure sample possesses the maximum band gap energy of 3.26 eV that is compatible with the literature for the thin film ZnO nanorods (Chanda et al, 2017; Narayanan & Deepak, 2018; Singh et al, 2017). Besides, Table 1 shows that the band gap energy is observed to decrease monotonously with the increment in the dopant addition level (especially the Al‐doped compounds).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The E g values calculated for all samples are numerically tabulated in Table 1. It is visible from the table that the pure sample possesses the maximum band gap energy of 3.26 eV that is compatible with the literature for the thin film ZnO nanorods (Chanda et al, 2017; Narayanan & Deepak, 2018; Singh et al, 2017). Besides, Table 1 shows that the band gap energy is observed to decrease monotonously with the increment in the dopant addition level (especially the Al‐doped compounds).…”
Section: Resultssupporting
confidence: 89%
“…The band gap value is calculated using α value and the following equation: numerically tabulated in Table 1. It is visible from the table that the pure sample possesses the maximum band gap energy of 3.26 eV that is compatible with the literature for the thin film ZnO nanorods (Chanda et al, 2017;Narayanan & Deepak, 2018;Singh et al, 2017).…”
Section: Optical Absorbance Spectra For Al-and Ni-doped Zno Samplessupporting
confidence: 89%
“…It is found that co-doping of B-N can effectively reduce the resistivity and further increase the carrier concentration. The Burstein-Moss effect increases the energy gap of the B-N co-doped film, thereby increasing the light utilization efficiency by stacking absorbers with different energy gaps (Nripasree et al, 2017). At present, co-doping ZnO with group III and V elements can be utilized to improve the acceptor solubility so as to enhance the electrical properties of the ZnO film (Yamamoto et al, 2001;Bian et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An ideal donor codopant is one that is not a ptype killer but is a reactive dopant that facilitates p-dopant incorporation and activation. 52 Boron, one such dopant, is used in this study as the donor codopant.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus is a preferred p-type dopant because of its large solubility relative to other dopants and its shallow acceptor level in ZnO; however, p-ZnO achieved in this manner has stability concerns. An ideal donor codopant is one that is not a p-type killer but is a reactive dopant that facilitates p-dopant incorporation and activation . Boron, one such dopant, is used in this study as the donor codopant.…”
Section: Introductionmentioning
confidence: 99%